2018
DOI: 10.1002/jssc.201800301
|View full text |Cite
|
Sign up to set email alerts
|

Influence of photoinduced isomerization on the chiral separation of novel liquid crystalline materials with a diazene moiety

Abstract: The influence of photoinduced isomerization on the enantiomeric separation of two newly synthesized liquid crystalline materials, liquid crystals 1 and 2, was studied by high-performance liquid chromatography on a chiral stationary phase Chiralpack AD-3. Both materials have one chiral center and one diazene moiety. The compounds were separated into their E and Z isomeric forms. The conditions and time scale of the ultraviolet-induced E to Z transition were briefly evaluated. Under the optimized conditions, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…The chiral separation method was based on a previously optimised methodology available in our laboratory for the enantioseparation of chiral photosensitive LCs [11,12,13]. Optimal separation conditions for precursors 2a – d were heptane/propan-2-ol (9/1, v / v ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The chiral separation method was based on a previously optimised methodology available in our laboratory for the enantioseparation of chiral photosensitive LCs [11,12,13]. Optimal separation conditions for precursors 2a – d were heptane/propan-2-ol (9/1, v / v ).…”
Section: Resultsmentioning
confidence: 99%
“…Although the optical purity of CLCs is a very important issue in the development and utilisation of novel chiral materials, only scarce information on chiral separation of CLCs can be found in the literature [9,10]. Most of the work thus far has been devoted to chiral liquid chromatography separation of photosensitive CLCs and the effect of light-induced E -to- Z -isomerisation on chiral recognition [11,12,13]. It has been found that the structure of CLCs plays an important role in the chiral resolution.…”
Section: Introductionmentioning
confidence: 99%